Calculation of Size-Specific Dose Estimation (SSDE) of The Pediatric's Head for Tube Current Modulation (TCM) CT Examinations. (March 2020) - Syaja'ah, K N; Anam, C; Lestari, F P; Haekal, M; Haryanto, F
Abstract: Computed Tomography (CT) examinations in the pediatric patient are sensitive to the impact of ionizing radiation, which gives long-term risk. In addition, the actual radiation dose delivered during CT examinations has not been well-described mainly when using tube current modulation (TCM) technique. To quantified this effect, an algorithm for calculating radiation dose is needed. Therefore, this study aims to calculate and analyze the estimated effective dose of head examinations from 3D CT images, based on the equivalent water diameter (Dw )For the TCM technique. Four pediatric patients in the 0-6-year-old age groups were examinations using Somatom Definition Flash with variation in the number of slices. CTDIvol and Tube current values were obtained from the DICOM header. There are two main parts algorithm for Dw calculation. First, images of CT data were converted to Hounsfield units (HU). Then, Dw values based on the patients contour using the K-mean cluster and morphological gradient algorithm were calculated for every slice. The coefficient factor is obtained by American Association of Physicists in Medicine (AAPM) report 220. The values then multiplied by CTDIvol to acquire values of SSDE. The results showed that the relation between SSDE and tube current was strongly correlated with R 2 values of 0.982.